Hollow nickel nanocorn arrays as three-dimensional and conductive support for metal oxides to boost supercapacitive performance - Chao, Dongliang (2014)
A novel three-dimensional (3D) metal/metal oxide core/branch array electrode has been fabricated as supercapacitor electrode. Hollow Ni nanocorn arrays are constructed on Ni foams and act as a highly conductive and stable support to Co3O4 nanoflakes. Enhanced pseudocapacitive performance compared to bare Co3O4 nanosheets is demonstrated with high rate capability and excellent cycling stability.